Long-Term Ecosystem Changes in Riparian Forests - Sakio, Hitoshi (Ecological Research Monographs,, 2020)
This open access book presents and analyzes the results of more than 30 years of long-term ecological research in riparian forest ecosystems with the aim of casting light on changes in the dynamics of riparian forests over time. The research, focusing on the Ooyamazawa riparian forest, one of the remaining old-growth forests in Japan, has yielded a number of interesting outcomes. First, it shows that large-scale disturbances afford various trees opportunities for regeneration and are thus the driving force for the coexistence of canopy trees in riparian forests. Second, it identifies changes in reproductive patterns, highlighting that seed production has in fact quantitatively increased over the past two decades. Third, it describes the decline in forest floor vegetation caused by deer grazing and reveals how this decline has affected bird and insect populations. The book illustrates the interconnectedness of phenomena within an ecosystem and the resultant potential for cascade effects and also stresses the need for long-term ecological studies of climate change impacts on forests. It will be of interest to both professionals and academics in the field of forest science. .